2013
DOI: 10.4014/kjmb.1311.11001
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Antioxidant Activity and Whitening Effects of Dendropanax morbifera Leaf Extracts

Abstract: In this study, we investigated the antioxidant activities on HaCaT and the whitening effects on B16F1 melanoma cells of Dendropanax morbifera leaf extract. In an antioxidative activity assay using HaCaT cells, the ethyl acetate (50 μg/ml) and aglycone fractions (25 μg/ml) of the D. morbifera leaf extract didn't exhibit any characteristics of cytotoxicity. When HaCaT cells were exposed to a single large dose (800 mJ/cm 2 ) of UVB, the extracts protected the cells against UVB radiation. When HaCaT cells were tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 10 publications
0
10
1
1
Order By: Relevance
“…The cytotoxicity test performed using Human keratinocyte cells in a previous study revealed that the Dendropanax morbifera Léveille leaf extracts exhibited no cytotoxicity at concentrations lower than 50 µm/mL. 36 This result was distinct from the results obtained using HNOK cells in this study; however, this is believed to be a result of the difference in cell sensitivities.…”
Section: Discussioncontrasting
confidence: 80%
“…The cytotoxicity test performed using Human keratinocyte cells in a previous study revealed that the Dendropanax morbifera Léveille leaf extracts exhibited no cytotoxicity at concentrations lower than 50 µm/mL. 36 This result was distinct from the results obtained using HNOK cells in this study; however, this is believed to be a result of the difference in cell sensitivities.…”
Section: Discussioncontrasting
confidence: 80%
“…Also, Maresca et al [27] reported that removal of ROS with antioxidants is effective in inhibiting melanin biosynthesis. A recent study reported that the ethyl acetate and aglycone fractions of Dendropanax morbifera leaf can act as skin cell protectants and natural antioxidants by protecting HaCaT cells against oxidative stress [28]. Moreover, treatment with the same fractions showed a better anti-melanogenic effect than arbutin, used as a positive control, against α-MSH-induced excessive melanin generation in B16/F10 melanoma cells [28].…”
Section: Discussionmentioning
confidence: 99%
“…D. morbifera , known as Dendro, means ‘omnipotent drug’ (Panax), and has been called the panacea tree. Various ongoing studies on D. morbifera are aiming to determine its medicinal uses (20–24). D. morbifera leaves are composed of 70.2% water, 1.2% protein, 2.7% fat, 1.7% ash, 56.9 mg% vitamin C and 746 mg% water soluble tannins; 32 types of substances have been identified with gas chromatography-mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that polyacetylene compounds isolated from D. morbifera leaves have anti-complement activity, whereas ethanol extracts promote the actions of B- and T-cells (20,23). D. morbifera sap inhibited melanin biosynthesis by reducing the expression of tyrosinase in melanin synthesis, and the ethyl acetate fraction extracted from D. morbifera leaves also exhibited cell protective and skin whitening effects, such as antioxidant properties and tyrosinase inhibition (24). However, few studies or animal experiments have been conducted on the mechanism underlying its anti-inflammatory properties.…”
Section: Introductionmentioning
confidence: 99%